Analysis of Multimedia Learning Mathematics Storyboard Design - Ike Yuliarni; Jefri Marzal; Eko Kuntarto (International Journal of Trends in Mathematics Education Research, 2019)
This study aims to describe the characteristics of storyboard design and to find out the multimedia storyboard design of mathematics learning in the production of BTIKP (Center for Information and Communication Technology Education) of the Jambi Provincial Education Office according to the rules based on ADDIE framework learning design. The researcher uses the ADDIE framework learning design because this design is more effectively used as a reference for the creation and development of a learning media. From the results of the identification carried out by the researcher in three stages. For the characteristics of the multimedia storyboard design of mathematics learning produced by the BTIKP (Center for Educational Information and Communication Technology) of the Jambi Provincial Education Office, there is one storyboard that satisfies the assessment, namely in the third stage (evaluating and revising) for multimedia storyboards learning mathematics with Geometry Transformation material. Overall the design of the five multimedia storyboards of mathematics learning produced by the BTIKP (Center for Educational Information and Communication Technology) of the Jambi Provincial Education Office which has been investigated by researchers is still a design that is not in accordance with the design of ADDIE framework learning.